2005
DOI: 10.1016/j.clpt.2005.03.006
|View full text |Cite
|
Sign up to set email alerts
|

High-dose statins and skeletal muscle metabolism in humans: A randomized, controlled trial

Abstract: High-dose statin treatment leads to changes in the skeletal muscle sterol metabolism. Furthermore, aggressive statin treatment may affect mitochondrial volume.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
157
5
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 276 publications
(176 citation statements)
references
References 38 publications
12
157
5
2
Order By: Relevance
“…Because the aim of our study was to collect preliminary data for a larger randomized trial, we elected not to perform muscle biopsies. Serum CoQ 10 was not measured because it is well known that CoQ 10 levels in blood correlate poorly with intramuscular levels (Paiva et al 2005). In contrast to Thompson et al(1997), we did not find an exacerbation of exercise-induced skeletal muscle injury after statin treatment.…”
Section: Discussioncontrasting
confidence: 45%
See 2 more Smart Citations
“…Because the aim of our study was to collect preliminary data for a larger randomized trial, we elected not to perform muscle biopsies. Serum CoQ 10 was not measured because it is well known that CoQ 10 levels in blood correlate poorly with intramuscular levels (Paiva et al 2005). In contrast to Thompson et al(1997), we did not find an exacerbation of exercise-induced skeletal muscle injury after statin treatment.…”
Section: Discussioncontrasting
confidence: 45%
“…Substantial reduction in intramuscular CoQ 10 levels were associated with decreased citrate synthase activity as well as decreased respiratory chain enzymes, suggesting diminished mitochondrial number and/or volume (Paiva et al 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In skeletal muscle, as the decrease of ubiquinone levels is thought to be one of the causative phenomena of muscle disorders, evaluation of the effect of statins on ubiquinone levels in skeletal muscle is considered useful to predict the possibility that statins will cause the development of myopathy. In humans, simvastatin at low doses (20 mg/d) did not decrease skeletal muscle ubiquinone 35,36) , but highdose treatment with simvastatin (80 mg/d) decreased ubiquinone levels in human skeletal muscle and decreased respiratory chain enzyme activity in a minority of patients with a substantial reduction in the muscle ubiquinone level 13) . In that study, simvastatin and atorvastatin similarly reduced cholesterol and ubiquinone levels in serum, but only simvastatin treatment reduced skeletal muscle ubiquinone levels.…”
Section: Discussionmentioning
confidence: 99%
“…Also, neither mitochondrial dysfunction nor a decrease in ubiquinone levels was correlated with histological changes in cerivastatin-treated rat muscle. On the other hand, just recently, it has been reported that high-dose treatment with simvastatin (80 mg/d) decreased ubiquinone levels in human skeletal muscle and decreased respiratory chain enzyme activity in a minority of patients with a substantial reduction in muscle ubiquinone level 13) . In addition, because ubiquinones play an important role in the mitochondrial respiratory chain, the possibility of the influence of statins on the myocardial energy generating system and the risk of cardiac dysfunction associated with a decreased cardiac ubiquinone level have been pointed out [14][15][16] .…”
Section: Introductionmentioning
confidence: 99%